Study protocol for a randomised controlled trial assessing the clinical and cost-effectiveness of the Journeying through Dementia (JtD) intervention compared to usual care - Wright, Jessica; Foster, Alexis; Cooper, Cindy; Sprange, Kirsty; Walters, Stephen; Berry, Katherine; Moniz-Cook, Esme; Loban, Amanda; Young, Tracey Anne; Craig, Claire; Dening, Tom; Lee, Ellen; et al. (BMJ open, 2019)
IntroductionServices are being encouraged to provide postdiagnostic treatment to those with dementia but the availability of evidence-based interventions following diagnosis has not kept pace with increase in demand. To address this need, the Journeying through Dementia (JtD) intervention was created. A randomised controlled trial (RCT), based on a pilot study, is in progress.Methods and analysisThe RCT is a pragmatic, two-arm, parallel group trial designed to test the clinical and cost-effectiveness of JtD compared with usual care. Recruitment will be through NHS services, third sector organisations and Join Dementia Research. The sample size is 486 randomised (243 to usual care and 243 to the intervention usual care). Participants can choose to ask a friend or relative (supporter) to become involved in the study. The primary outcome measure for participants is Dementia-Related Quality of Life (DEMQOL), collected at baseline and at 8 months’ postrandomisation. Secondary outcome measures will be collected from participants and supporters at those visits. Participants will also be followed up at 12 months’ postrandomisation with a reduced set of measures. A process evaluation will be conducted through qualitative and fidelity substudies. Analyses will compare the two arms of the trial on an intention to treat as allocated basis. The primary analyses will compare the mean DEMQOL scores of the participants at 8 months between the two study arms. A cost-effectiveness analysis will consider the incremental cost per Quality Adjusted Life Years of the intervention compared with usual care. Qualitative and fidelity substudies will be analysed through framework analysis and fidelity assessment tools respectively.Ethics and disseminationREC and HRA approval were obtained. A Data Monitoring and Ethics Committee has been constituted. Dissemination will be via publications, conferences and social media. Intervention materials will be made open access.Trial registration number ISRCTN17993825.